Effect of snake venom derived fibrin glue on the tendon healing in dogs: clinical and biomechanical study - Ferraro,G. C. (2005)
The aim of this study was to evaluate the effect of snake venom derived fibrin glue on the strength oftendon healing in dogs. The deep digital flexor tendon of the 5th digit of 24 thoracic limbs was partially sectioned for adhesive application. On the 7th, 15th, and 30th postoperative day tendons segments were removed for the clinical and biomechanical study. Results indicated that 62.5% of the tendons showed stump retraction and 20.8% moderate to excessive adherence, which affected gliding. The biomechanical evaluation showed that, over time, tendon healing gained progressive resistance for maximum traction and permanent deformations with satisfactory results on the 15th day for rigidity and resilience compared to the other two studied periods. Snake venom derived fibrin glue promotes healing in dog flexor tendon.